Van natuurlandschap tot risicomaatschappij De geografie van de relatie tussen mens en milieu - Dietz, Ton (Amsterdam University Press, 2008)
This study is an illustrated overview of the relationship between people and their environment worldwide. It is not only about the natural aspects of agricultural production; the authors also adress the non-material benefits of a healthy natural environment. The book has a preface by Ruud Lubbers, former prime minister of the Netherlands.